The Granger-Causality between Transportation and GDP: A Panel Data Approach - Mehmet Aldonat Beyzatlar; Müge Karacal; I. Hakan Yetkiner (Izmir University of Economics, Department of Economics, 2012)
This study investigates the Granger-causality relationship between real per capita GDP and transportation of EU-15 countries using a panel data set covering the period 1970-2008. Our findings indicate that the dominant type of Granger-causality is bidirectional. Accordingly, we conclude that care must be paid in defining the dependent and independent variables when studying the relationship between transportation and income. Instances of one-way or no Granger-causality were found to correspond with countries with the lowest income per capita ranks in 1970 and/or in 2008, including Portugal, Greece and Italy. We speculate that bi-directional Granger causality between income and transportation is observed only after an economy has completed its transition in terms of economic development.
Keywords: C23; O18; 330; Granger-causality; Transportation; Income; Nationaleinkommen; Verkehrsinfrastruktur; Kausalanalyse; Schätzung; EU-Staaten